Affective Empathy in Behavioral Variant Frontotemporal Dementia: A Meta-Analysis - Carr, Andrew R.; Mendez, Mario F. (Frontiers in Neurology, 2018)
Background: Empathy deficits are a widely recognized symptom in the behavioural variant frontotemporal dementia (bvFTD), and although several reviews have examined cognitive empathy deficits, there are no meta-analytic studies on affective empathy deficits. Objective: Identify salience of affective empathy in bvFTD. Method: A thorough review of affective empathy found 139 possible studies, but only 10 studies included measures of affective empathy and met standardized criteria. Results: BvFTD patients demonstrated a modest impairment compared to controls across all tasks (d = 0.98). Empathic concern as measured by the interpersonal reactivity index was particularly effected (d = 1.12). Conclusions: This study provides evidence for an increased commitment to observing affective empathy in bvFTD and capturing its role in the disorder.